Photovoltaic/spectrum performance analysis of a multifunctional solid spectral splitting covering for passive solar greenhouse roof. (1st January 2022) - Ma, Qianlei; Zhang, Yi; Wu, Gang; Yang, Qichang; Yuan, Yu; Cheng, Ruifeng; Tong, Yuxin; Fang, Hui
Graphical abstract: Highlights: A novel spectral splitting covering applied in greenhouse is proposed. The cascade utilization of full-spectrum solar energy in greenhouse is achieved. The light competing problem of photovoltaic and photosynthesis is solved. Presented covering can effectively reduce the cooling energy consumption in greenhouse. Abstract: Full-spectrum efficient conversion is one of the international frontiers research in the field of greenhouse engineering. Visible light (400–780 nm) is critical for driving the photosynthesis process of greenhouse plants, but near-infrared spectrum (780–2500 nm) have little contributions and may cause overheating. In this research, a novel greenhouse covering structure named as the spectral splitting covering is designed which can transmit visible light and convert near-infrared light into electricity. The working principle of this covering and the design and analysis of structure parameters are introduced, and meanwhile, a numerical simulation of the light path variation of internal structure and the optical characteristics of the device are also provided. Based on the simulation results, the visible light transmissivity and the electric power of this covering were measured under the actual weather condition. The energy analysis and performance estimation of the system are provided at last. The results show that the simulated transmissivity was in good agreement with the experimental values, and the all-day visible light transmissivity was above 40% and the maximum reached 57.7%. The electric power of this covering shows a trend of being high at noon and low in the morning and evening. The maximum value was 133.2 W∙m −2 and the full-day photovoltaic efficiency was 6.88%. The visible light energy entering the greenhouse was 4.49 MJ∙m −2 ·d −1 for crop photosynthesis, and this covering can effectively reduce the cooling energy consumption in greenhouse with the 78% near-infrared blocking rate. It can be proved that this new covering can ensure the plant growth and convert the near-infrared light into electricity without the solar tracking system, which realizes the concentrating spectral splitting utilization and provides a new approach for improving the comprehensive utilization of full-spectrum solar energy in the greenhouse.